Multi-omics analysis of lactate metabolism gene regulation in Clonorchis sinensis-associated hepatocellular carcinoma - Qiumei Lin; Junxian Chen; Lingling Zhou; Min Fang; Caibiao Wei; Taijun Huang; Yulong Xu; Jie Gao; Fengfei Liu; Zeli Tang; Jian-Kang Zhu; Weilong Yang (Parasites & Vectors)
Abstract Background Although recent research has highlighted lactylation, a post-translational modification driven by elevated lactate levels, as a critical regulator of key cellular pathways in hepatocellular carcinoma (HCC), its contribution to the poor prognosis of Clonorchis sinensis (Cs)-infected HCC remains poorly understood. Methods We first identified the significant upregulation of the lactate metabolism enzyme LDH in Cs-infected HCC patients through clinical retrospective analysis. We then conducted a multi-omics analysis (RNA-Seq, ATAC-Seq, WGBS-Seq, oxWGBS-Seq, and ChIP-Seq) to examine the differences in 392 lactate metabolism-related genes (LMRGs) between Cs-infected and Cs-noninfected HCC tumors. Six key differentially expressed LMRGs were further validated using RT-qPCR assays to confirm their expression and potential role in HCC progression. Results The differential expression levels of 8 LMRGs, along with 71 accessible regions and 42 CpG sites in the promoters of LMRGs, were identified. Notably, we also demonstrated that histone modifications, including H3K9ac, H3K79me2, H3K4me2, H3K4me3, H3K27ac, and H3K4me1, were associated with chromatin accessibility in the promoters of LMRGs. Finally, the TCGA-LIHC cohort confirmed that the differential expression of LMRGs between Cs-infected and Cs-noninfected HCC tumors significantly affects the survival outcomes of HCC. Conclusions Our findings revealed that lactylation plays an important role in reshaping the characteristics of HCC during Cs infection, expanding our understanding of the unique features of Cs-infected HCC. Graphical Abstract